The effectiveness of group guidance services using the Gestalt Counseling Approach with projection techniques in preventing bullying among students - Kiki Elfi Lestari; Firman Firman (International Journal of Applied Counseling and Social Sciences, 2021)
Bullying behavior is an act that violates the strength and power that is hurting someone who is weaker verbally, physically, or psychologically so that the victim feels under pressure and tends to be helpless. Factors that influence the occurrence of bullying behavior are the influence of the school environment, peer groups, social environmental conditions and television shows and social media. So that efforts are needed to prevent bullying behavior among students. One way that can be done to prevent bullying behavior among students is to provide group guidance services using the Gestalt approach with projection techniques. This study aims to test the effectiveness of group guidance services using the Gestalt approach with projection techniques in preventing bullying among students. The findings of this study are: (1) there is a significant difference in bullying behavior in the experimental group before and after attending group guidance services using the Gestalt approach with projection techniques (2) there is a significant difference in bullying behavior in the control group before and after being given group guidance services on bullying behavior without special treatment, (3) There are differences in the bullying behavior of experimental group students who are treated with group guidance services using the Gestalt approach with projection techniques with the control group who are given group guidance services about bullying behavior without special treatment, this can be seen in the posttest average score of the experimental group dropped higher than the mean posttest score of the control group.